Diaspora engagement: a scoping review of diaspora involvement with strengthening health systems of their origin country. Issue 1 (1st January 2022) - Taslakian, Editt N.; Garber, Kent; Shekherdimian, Shant
ABSTRACT: Background: Diaspora communities are a growing source of external aid and resources to address unmet needs of health systems of their homelands. Although numerous articles have been published, these endeavors as a whole have not been systematically assessed. Objective: Examine the available literature to assess activities through which diasporas engage with the health system in their origin country and what barriers they face in their interventions. Methods: This is a scoping review from 1990–2018 using the PRISMA-Scr framework to examine both peer-reviewed and gray literature on (1) specific activities through which diasporas contribute to the health system in their origin country; (2) major health needs diasporas have tried to address; and (3) barriers faced by diaspora healthcare efforts. Results: The initial search identified 119 articles, of which 45 were eligible after excluding non-relevant studies. These were case studies of diaspora contributions to health systems in their origin country (13), interviews (13), literature reviews (9), general articles on the topic (4), and correspondences or presentations (6). The healthcare needs diasporas have sought to address include health workforce emigration ('brain drain') (10), capacity building for research and training (10), inadequate infrastructure (5), and finances (4). Specific activities included short-term missions (11), establishing partnerships (9), emigration back to country of origin (8), specific research and training programs (8), and financial remittances (5). Specific barriers identified were most commonly financial need within the origin country (8), lack of sustainability (6), communication issues (6), lack of intention to return to the origin country (5), infrastructure (4), and political concerns (3). Conclusion: Further research on how to expand the scope of and reduce barriers to diaspora engagement is needed to optimize the effectiveness of diaspora contributions to their origin countries. Metrics and standards should be developed for assessing impact of diaspora engagement and interventions.